Priporočila za odkrivanje in zdravljenje Fabryjeve bolezni v Sloveniji - Vujkovac, Bojan (Zdravniški vestnik, 2006)
Background Fabry disease is a rare X-chromosome linked disease. Due to gene mutation, activity of enzyme agalactosidase A is lowered or absent and sphingolipids care deposited in different organ cells. All males with gene mutation are affected but females too, due to X chromosome inactivation, can frequently be affected as well, although usually to a lesser extend. Disease is slowly progressive and there is an early dysfunction of several organs, specially endothelium, kidney, heart and central nervous system, which all leads to early death of the patient. Conclusions Recently, a specific enzyme replacement therapy, based on recombinant technology, was discovered. Specific therapy is effective and safe. Due to a new therapy there was a need to set objective criteria when to start with enzyme replacement therapy, but also a need to more complex, multidisciplinary approach to those patients. This article is an initial proposal for systematic management of Fabry diseasein our country.
Keywords: dedne bolezni; Diagnosis; diagnostika; Fabryjeva bolezen; Fabry's Disease; Practice Guidelines; Praktična navodila; Therapy; zdravljenje